1980
DOI: 10.1177/00220345800590050501
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Fluoride Intake of Average Two-year-old Children in Four Dietary Regions of the United States

Abstract: Analysis of toddler "Market Basket" food collections indicates that an average two-year-old child living in cities with water supplies containing 0.37 to 1.04 ppm of fluoride has a daily fluoride intake of 0.315 to 0.610 mg/day (0.025 to 0.049 mg/kg body weight) from food, water, and beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…The range for average daily intake by two-year-old children is only slightly higher and also depends strongly on the drinking water fluoride concentration (Ophaug et al, 1980b(Ophaug et al, , 1985. These findings are in close agreement with those of Dabeka et al (1982) and Featherstone and Shields (1988).…”
Section: Fluoride Intakesupporting
confidence: 91%
“…The range for average daily intake by two-year-old children is only slightly higher and also depends strongly on the drinking water fluoride concentration (Ophaug et al, 1980b(Ophaug et al, , 1985. These findings are in close agreement with those of Dabeka et al (1982) and Featherstone and Shields (1988).…”
Section: Fluoride Intakesupporting
confidence: 91%
“…A 1980 analysis of ‘market basket’ food collections found that 2‐year‐olds living in regions of the US, with water fluoride levels between 0.37 and 1.04 g/l, ingested between 0.025 and 0.049 mg F/kg/day from foods, water and beverages (13): dietary fluoride intake comparable to that estimated in this study. More recently, a study, which utilized two, 3‐day diet diaries to collect information about dietary intake and conducted fluoride analyses of ingested foods, also estimated that 4‐year‐old children living in a negligibly fluoridated area of Iran (0.3 mg F/l) ingested 0.413 ± 21 mg F/day (0.028 mg F/kg/day) from their diet (44).…”
Section: Discussionsupporting
confidence: 73%
“…In theory, its action in the prevention of caries is topical and no ingestion of toothpaste is necessary. However, ingestion of toothpaste foam is unavoidable, all the more so in young children (Ophaug et al 1980). The ingestion of fluoridated toothpaste is a relatively major contributor to total fluoride ingestion in young children in fluoridated and non-fluoridated water supply areas (Zoohouri et al 2012).…”
Section: Prevention Of Caries Among Australian Childrenmentioning
confidence: 99%